2004
DOI: 10.1103/physrevlett.93.196103
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Surface Reactivity via Electron Quantum Confinement

Abstract: The effect of electron quantum confinement on the surface reactivity of ultrathin metal films is explored by comparing the initial oxidation rate of atomically flat magnesium films of different thickness, using complementary microscopy techniques. Pronounced thickness-dependent variations in the oxidation rate are observed for well ordered films of up to 15 atomic layers. Quantitative comparison reveals direct correlation between the surface reactivity and the periodic changes in the density of electronic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
119
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 30 publications
8
119
1
Order By: Relevance
“…Such properties of nanostructured materials are usually attributed to quantum size effects (QSE). However, the materials used in most previous studies suffer from size fluctuation, resulting in not well defined material properties, and hence the evidences for QSE are at best qualitative (4). In the case of thin films, a far more convincing proof of QSE would be the direct observation of an oscillatory dependence of the chemical reactivities on the film thickness, which is reported here.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Such properties of nanostructured materials are usually attributed to quantum size effects (QSE). However, the materials used in most previous studies suffer from size fluctuation, resulting in not well defined material properties, and hence the evidences for QSE are at best qualitative (4). In the case of thin films, a far more convincing proof of QSE would be the direct observation of an oscillatory dependence of the chemical reactivities on the film thickness, which is reported here.…”
mentioning
confidence: 72%
“…For example, in nature, Au is the most stable metal, yet a Au nanoparticle becomes chemically reactive (when the size is Ϸ3 nm) and can catalyze the oxidation of CO (1). Thin films are another such example where size-dependent surface chemical activities have been observed when the thickness is in the nanometer scale (3,4). Such properties of nanostructured materials are usually attributed to quantum size effects (QSE).…”
mentioning
confidence: 99%
“…In such films, the thicknesses are comparable to the electron coherence length, and quantum well states ͑QWSs͒ may form due to electron confinement in the direction normal to the surface. 1,2 Many physical properties therefore show a strong dependence on layer thickness, and such quantum size effects ͑QSEs͒ have been found to induce, and thus to be reflected in, the oscillation with the thickness of macroscopic properties such as sign and magnitude of the Hall effect, 3,4 reactivity and absorption, 5 the magnitude of the superconducting transition temperature, 6,7 and details of the growth morphology. 8 Moreover, the study of electron confinement in metal films has contributed to an understanding of basic solid-state physics phenomena such as electronphonon coupling.…”
mentioning
confidence: 99%
“…On the fundamental side, efforts have been focused on controlling the formation of novel nanostructures through manipulation of strain energy, adsorbate-modified kinetics, and light irradiation 1,2,3,4,5 . For ultra-thin metal epitaxy, emerging research over the last decade has demonstrated that quantum confinement of electronic states can have profound effects on the growth of various metal nanostructures as well as their physical and chemical properties 6,7,8,9,10,11,12,13 . This is commonly referred to as "quantum" or "electronic growth 14 .…”
Section: Introductionmentioning
confidence: 99%